Understanding abscisic acid-mediated stress signaling to affect rice development under stress - Gul, Rao Muhammad Samran; Rauf, Saeed; Ortiz, Rodomiro; Waqas Khalid, Muhammad; Kaya, Yalcin (Frontiers in Sustainable Food Systems, 2024)
Introduction Rice is a vital staple food for many countries, and its yield is known to be significantly affected by various abiotic stresses, which are expected to intensify with climate change, posing a threat to global food security. Abscisic acid (ABA), a crucial plant growth regulator, plays a crucial role in plant responses to these abiotic stresses. It influences several processes, such as seed dormancy, leaf gas exchange, reactive oxygen species (ROS) scavenging, ion toxicity reduction, and root elongation, all of which contribute to enhancing plant survival under stress. Methods This article reviews recent research on ABA-mediated gene responses and expressions involved in rice plant architecture and its response to abiotic stress. Results and discussion Abscisic acid responses were primarily driven by changes in gene expression. Expression analyses of the gene related to ABA biosynthesis or catabolism indicated several changes in plant architecture, such as changes in leaf angle, delayed flowering, and modifications in growth regulators. Additionally, tolerance-related mechanisms, such as increased ROS scavenging, reduced membrane leakage, and vacuolar compartmentation of toxic radicals, were activated under single or multiple stress conditions. While these adaptations may improve plant survival and yield sustainability under stress, they may not necessarily enhance yield potential in environments affected by drought, salinity, or heat stress. ABA expression was also associated with improved pollen viability, grain-filling potential, and seed setting under abiotic stresses such as heat, which could enhance seed yield in such challenging environments.